A cooperative phase-steering technique in spectrum sharing-based military mobile ad hoc networks - Sangku Lee; Janghyuk Youn; Bang Chul Jung (ICT Express, 2020)
In military applications, mobile ad hoc networks are commonly used due to the autonomy, self-configuration, and flexibility. In addition, spectrum sharing-based communication protocols are being actively considered due to spectrum shortage. We propose a cooperative phase-steering (CPS) technique for a spectrum sharing-based military mobile ad hoc network which consists of a single secondary source (SS) node, multiple secondary relay (SR) nodes, a single secondary destination (SD) node, and multiple primary destination (PD) nodes. In the proposed technique, the SR nodes that succeeded the packet decoding cooperatively adjust the phase of their transmit signals such that the received signals at the SD node from the SR nodes are aligned to a certain angle, while the SR nodes control the transmit power such that the received power at all PD nodes is lower than a certain threshold. Through extensive computer simulations, it is shown that the proposed technique outperforms the conventional cooperative relaying scheme in terms of outage probability.